(untitled) (GEON Journal (Management, Organizations and Business), 2020)
The review article is framed within the development of a research project entitled “Perception of the professional of Public Accounting from photography and cinema as cultural expressions”; and its objective is to establish a conceptual approach to the categories: Professional of Public Accounting and Culture and two photography and cinema subcategories, as theoretical tools for analysis of research results. The interest is motivated in the reflections of professionals and students in training of the Public Accounting and its relationship with society and the construction of Culture. Reviews are mostly accomplished in Google Scholar, repositories and part in databases like Redalyc, Academia and Scielo. The main contribution that is achieved is the consolidation of the proposal around the professional of Public Accounting and his relationship with society; as well as the creation of stereotypes elaborated from tools that help to consolidate culture such as photography and cinema.